The Effect of Styrofoam on the Corrosion of Steel Reinforced Concrete - Kelestemur, Oguzhan; Yildiz, Servet (Gazi Univ, 2005)
In this study, the corrosion of steel reinforced into the concrete samples and obtained with the addition of styrofoam which was replacing 5, 10 and 15% of the agregate volume in the concrete structure was investigated. 3% NaCl which was base for seawater was added into the solution water of the concrete mortar for the sake of creating corrosive environment and then the tests have been carried out. The corrosion rates were measured according to the galvanic current method on the samples. The corrosion potentials have been measured by applying ASTM-C-876-91 method for 90 days and using Cu/CuSO4 reference electrode. As a result of these experiments, it is found that the corrosion rate of steels reinforced into the concrete increased and compressive strength of concrete samples decreased with the increasing of the portion of styrofoam.
Keywords: Corrosion; Styrofoam; Reinforced concrete; Steel